Effect of couples 'online training on maternal-fetal attachment in pregnant women - Elieh Abasi; Narjes Sadat Borghei; Shahrbanoo Goli; Maryam Farjamfar; Afsaneh Keramat (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Due to the importance of maternal fetal attachment (MFA) in women mental health improvement and considering the fathers' role in MFA promoting, this study conducted to investigate the effect of couple education on maternal fetal attachment. MATERIALS AND METHOD: This randomized controlled trial was conducted on 100 pregnant women and their husbands referred to six health centers in Sari from May to June 2021. The sampling method was stratified random sampling. Data collection tools included demographic information form and the Cranley MFA Scale with 24 questions. The intervention group took part in four session's weekly training about spouse support, attachment behaviors, and gender preference of parents, while the control group received only the routine antenatal care. Both groups completed Cranley's questionnaire before and 4 weeks after the intervention. Data were analyzed using Chi-square test, Fisher's exact test, paired and independent t-test by SPSS 21. RESULTS: MFA mean scores, pre-training and post-training in intervention group were 3.27 (0.54) and 3.75 (0.42), respectively; in the control group, were, 3.24 (0.49) and 3.21 (0.48). There was a significant difference between the two groups' MFA mean scores after intervention (P < 0.001). CONCLUSION: The findings of this study revealed that couple training regarding spouse support, attachment behaviors, and gender preference during pregnancy can promotes MFA even online training.